Aktivitas Hepatoprotektor Batang Fibraure tinctoria Lour Secara In Vivo - Ika Fikriah (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2012)
Study on Fibraurea tinctoria Lour (FT) stems gives information about its traditional utility as yellow fever treatment. Research of antecedent of FT stem proved that inhibited lipid peroxidation more effective than tocopherol acetate. These study was intended to prove hepatoprotector activity of ethanolic FT stem extract by in vivo. FT stem extract was macerated using absolute ethanol during 5 days that was repeated 3 times . FT stem extract hepatoprotector activity by in vivo was tested using carbon tetrachloride induced hepatotoxicity on Wistar rat. They were given FT stem extract orally once a day at dose 50, 100, and 200 mg/kgBW and Curcumin at dose 50 mg/KgBW as positive control. After 10 days, all groups were examined liver function (SGOT, SGPT, ALP), liver Malonedialdehide (MDA) level by Thiobarbituric acid method, and liver histopathology by Haemotoxylin-Eosin staining. Group that induced by CCl4 showed significant elevation of SGOT, SGPT and ALT also Liver MDA than group control. FT stem extract treatment inhibited elevation of SGOT, SGPT, ALT and Liver MDA significantly.Qualitative histopathological examination on Group 2 showed extensive fibrosis and necrosis, along with periportal PMN and lymphocyte infiltration. FT stem extract treatment inhibited pathological change that was induced by CCl4. Dose elevation showed tendency of stronger inhibition on liver cell tissue destruction and inflammation. Key words: Fibraurea tinctoria, hepatoprotector, in vivo Abstrak Penelusuran secara etnobotani, batang Fibraurea tinctoria Lour (FT) digunakan untuk obat sakit kuning. Penelitian pendahuluan batang FT berkemampuan meredam peningkatan lipid peroksidasi secara in vitro yang lebih kuat dibandingkan dengan tokoferol asetat. Membuktikan khasiat ekstrak etanol batang FT sebagai hepatoprotektor secara in vivo. Batang FT dimaserasi dengan etanol absolut selama 3 x 5 hari. Uji hambatan kerusakan hati secara in vivo digunakan model tikus yang diinduksi karbon tetraklorida (CCL4), ekstrak etanol FT diberikan dengan dosis 50, 100, 200 mg/KgBB sekali sehari dan curcumin dosis 50 mg/KgBB sebagai kontrol positif selama 10 hari lalu diperiksa fungsi hati (serum SGOT, SGPT dan ALP), kadar malondialdehida hati (MDA-hati), serta pemeriksaan patologi anatomi hati dengan pewarnaan Hematoksilin Eosin (HE). Kelompok tikus yang diinduksi CCl4 memperlihatkan peningkatan nilai SGOT, SGPT dan ALT dan MDA-Hati secara bermakna dibandingkan dengan kontrol. Pemberian ekstrak etanol batang FT secara oral dapat melemahkan peningkatkan nilai SGOT, SGPT dan ALT serta dapat menghambat peningkatkan nilai MDA-Hati pada tikus yang diinduksi CCl4 secara bermakna. Hasil pemeriksaan PA menunjukkan fibrosis dan nekrosis yang luas disertai infiltrasi sel-sel PMN dan limfosit di daerah periportal pada kelompok tikus yang diinduksi CCl4 > Curcumin > FT 50 > FT 100 > FT 200 mg/KgBB. Kata Kunci: Fibraurea tinctoria, Hepatoprotektor, in vivo